Development of Student Worksheets on Biology Topics Based on Critical Thinking Skills - Hairunnisa Hairunnisa; Muhammad Zaini; Badruzsaufari Badruzsaufari; Mohamad Nor Aufa; Yenny Warnida; Muhammad Hasbie (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to develop student worksheets based on critical thinking skills for seventh-grade students in junior high school. Development is carried out by means of Education Design Research (EDR). This article describes the results of the validity and practicality of worksheets based on critical thinking skills. The data collection technique used is a test questionnaire. The instruments used in this study were students' validity and practicality questionnaires. Data analysis techniques include analysis of data validity, data, and practicality (practical content, expectations, and actual). The worksheets validation sheet based on critical thinking skills was given to 5 validators consisting of 3 education experts and 2 science teachers in public junior high school 12 Banjarmasin. Three students filled out the questionnaire on the practicality of the contents of the worksheets through the one to one evaluation test, nine students filled out the practicality of the expectations of the worksheets through the small group evaluation test, and thirty-two students of the developed worksheets filled out the actual practicality of the worksheets. The results of the analysis of the validity of the questionnaire concluded that the validity of the worksheets was 3.60 valid categories. The results of the practicality of the contents are 3.84 in the practical category, the practicality of hope is 95.90 in the practical category, and the actual practicality is 96.06 in the practical category. This means that the worksheets based on critical thinking skills are valid and practical in the learning process to practice critical thinking skills